Teachers’ strategy in conducting assessments in the new normal era - Gupitasari, Venie; Retnawati, Heri (Journal of Education and Learning (EduLearn), 2024)
Assessment is an important component of learning which aims to determine student achievement in learning. However, the pandemic has changed how assessment is carried out, prompting teachers to look for new strategies in carrying out mathematics learning assessments under any conditions, whether in normal conditions or during a pandemic. This study described the strategies used by high school mathematics teachers in assessing mathematics learning during the pandemic towards the post-pandemic period. This type of research is descriptive exploratory research with a qualitative approach. The subjects in this study were three mathematics teachers, three principals, and three vice principals from a public senior high school in Yogyakarta City, Indonesia. Qualitative data were collected by means of questionnaires, interviews, and documentation. The collected data were analyzed qualitatively according to Bogdan and Biklen. The results of the study reveal that the mathematics teacher’s strategy for carrying out assessments during a pandemic includes: i) determining the appropriate online assessment platform that suits the needs; ii) assessment based on student participation; iii) using various of online assessment methods; iv) prioritizing academic integrity and honesty in the assessment implementation; and v) carry out the management and reporting of data on the results of the assessment in accordance with established procedures.